Bank loan supply shocks and alternative financing of non-financial corporations in the euro area - Martin Mandler; Michael Scharnagl (Deutsche Bundesbank, 2019)
We analyse the macroeconomic effects of exogenous contractions in bank lending to non-financial corporations in the Euro Area, Germany, France, Italy and Spain using a Bayesian vector autoregressive model with endogenous hyperparameter selection and identification via sign restrictions. We focus on the behaviour of firms' external financing sources alternative to bank loans, such as financing via equity, debt securities, trade credit and lending from non-banks. We investigate whether these alternative financing sources are complements to or substitutes for bank lending using the joint posterior distribution of their impulse responses with that of bank loans. For the Euro Area our results show equity, debt securities and non-bank loans to be substitutes for bank loans with negative responses to a positive loan supply shock while trade credit is a complement and responds positively. We show that the substitution relationship with respect to bank loans is more clearly visible in the joint distribution of the financing sources reactions than when focusing only on the marginal impulse responses. Quantitatively, the developments in bank loans and trade credit dominate the response of the overall sum of the external financing. This result also holds in most cases at the country level. However, whether and which of the alternative financing sources are substitutes for or complements to bank loans differs across countries.
Keywords: C32; E32; E51; 330; loan supply; external financing; Euro Area; Bayesian VAR; sign restrictions; joint posterior distribution